2013
DOI: 10.1177/0269215513484772
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of aquatic physical therapy in the treatment of fibromyalgia: a systematic review with meta-analysis

Abstract: Three meta-analyses showed statistically significant results in favour of the aquatic physical therapy (Fibromyalgia Impact Questionnaire, stiffness and the 6-minute walk test) during a period of longer than 20 weeks. Due to the low methodological rigor, the results were insufficient to demonstrate statistical and clinical differences in most of the outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 45 publications
1
14
0
2
Order By: Relevance
“…Similarly, Naumann et al 24 found moderate-to-strong evidence that therapeutic BT resulted in small improvements in pain and health-related QoL in patients with fibromyalgia. Lima et al 25 also reported that aquatic therapy had significant effects on physical function, QoL, and stiffness in patients with fibromyalgia during a period of longer than 20 weeks. Liu et al 26 observed that mud therapy was a favorable option for pain relief in patients with knee OA.…”
Section: Study Selection and Characteristics (Conclusion On Each Study)mentioning
confidence: 98%
“…Similarly, Naumann et al 24 found moderate-to-strong evidence that therapeutic BT resulted in small improvements in pain and health-related QoL in patients with fibromyalgia. Lima et al 25 also reported that aquatic therapy had significant effects on physical function, QoL, and stiffness in patients with fibromyalgia during a period of longer than 20 weeks. Liu et al 26 observed that mud therapy was a favorable option for pain relief in patients with knee OA.…”
Section: Study Selection and Characteristics (Conclusion On Each Study)mentioning
confidence: 98%
“…In particular, the participants in this study wanted more hydrotherapy after they had completed the programme, highlighting that two sessions were not enough. Aquatic physiotherapy or hydrotherapy is often used as a way for people living with FM to safely and enjoyably increase their physical activity levels, improving physical function and the overall impact of the condition (Bidonde et al, 2014;Lima et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Fibromiyaljide hastaların hastalık ve gidişatı açısından bilgilendirilmesi tedaviye uyumunu ve iyileşme hızını arttırır (5) . (16) . Yine fizik tedavi modalitelerinden sıcak paketler, terapötik ultrason, Transkutanöz Elektrik Stimulasyon, düşük güçlü lazer uygulamalarının fibromiyalji hastalarının uyku düzenine olumlu katkı yaptığı gösteril-miştir (17) .…”
Section: Discussionunclassified